Garden planting irrigation device convenient to move - WANG YING; LI HONG; MA ZHE; WANG BAIBING; ZHANG YANG; CHEN LANFEN (2024)
The utility model discloses a garden planting irrigation device convenient to move, and relates to the technical field of irrigation. The extension pipe penetrates through the upper side of the water outlet pipe; the two square elbows are arranged at the front end and the rear end of the extension pipe respectively, and irrigation hoses are arranged in the vertical ends of the square elbows; the two lantern rings are respectively arranged on the irrigation hose in a sleeving manner; the driving motor is fixed to the inner wall of the right side of an open groove formed in the base. The driving gear sleeves and is fixed on an output shaft of the driving motor; the two driving blocks are arranged on the upper side and the lower side of the driving tooth block in a meshed mode correspondingly, and the driving blocks and the inner walls of the upper side and the lower side of the open groove are arranged in a sliding mode correspondingly. The upper boss is fixed to the rear side of a driving block on the upper si